2012
DOI: 10.1073/pnas.1120775109
|View full text |Cite
|
Sign up to set email alerts
|

The inexorable resistance of inertia determines the initial regime of drop coalescence

Abstract: Drop coalescence is central to diverse processes involving dispersions of drops in industrial, engineering, and scientific realms. During coalescence, two drops first touch and then merge as the liquid neck connecting them grows from initially microscopic scales to a size comparable to the drop diameters. The curvature of the interface is infinite at the point where the drops first make contact, and the flows that ensue as the two drops coalesce are intimately coupled to this singularity in the dynamics. Conve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
236
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(259 citation statements)
references
References 33 publications
(102 reference statements)
19
236
4
Order By: Relevance
“…As the membranes twist around each other, the connecting bridge expands in width, eventually producing a circularly shaped defect-free daughter membrane. In conventional coalescence, the rate of neck expansion is determined by hydrodynamic and inertial forces 3 . By contrast, the significantly slower neck expansion in membrane coalescence is dominated by the rate at which the two membranes rotate with respect to each other.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the membranes twist around each other, the connecting bridge expands in width, eventually producing a circularly shaped defect-free daughter membrane. In conventional coalescence, the rate of neck expansion is determined by hydrodynamic and inertial forces 3 . By contrast, the significantly slower neck expansion in membrane coalescence is dominated by the rate at which the two membranes rotate with respect to each other.…”
Section: Resultsmentioning
confidence: 99%
“…In order for the droplets to coalesce, a rupture must occur between two merging interfaces which, coupled with surface tension and hydrodynamic forces, leads to energetic barriers and non-trivial coalescence progression [1][2][3][4][5] . For complex fluids with partial positional and/or orientational order, the complexity of the coalescence reactions increases considerably 6 .…”
mentioning
confidence: 99%
“…The hydrodynamics of droplet coalescence can be explained in the context of diffusion or capillary forces [16], viscous forces [17][18][19][20], inertial forces [21,22] and interfacial forces [22,23]. Especially, droplet coalescence has been studied extensively for systems dealing with microfluidics [24][25][26][27] is retained on the sieve [31,32], centrifugation, Osmotic pressure, micromanipulation [33], rheology, turbidity and electro-kinetic [34].…”
Section: Breaking and Coalescencementioning
confidence: 99%
“…Paulsen et al used an electrical method and high-speed imaging to describe the droplets coalescence. They showed that the outer uid had a small e ect on the coalescence dynamics [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%